Retorika Pemerintah dan Respon Masyarakat Studi Kasus di Indonesia dan Filipina - Haba, John (P2KK LIPI, 1997)
Greg Acciaioli-Jenifer Nourse (eds). Official Rhetoric-Popular Response Dialogue and Resistance in Indonesia and Philippines, Adalaide: Social Analysis-Journal of Cultural and Social Pracites No.35, April 1994. 164 Halaman